Answer:
Answer is attached to the picture
hope this helps
brainliest appreciated
good luck! have a nice day!
Look at the attached picture
Hope it will help you.
Answer:
110%
Step-by-step explanation:
Answer:
I wanna say its 51% but I'm not sure! Wait for another answer to verify^^
The value of the expression 3 - 3x6 + 2 is -13.
Given,
3-3x6+2
We need to solve this given expression.
PEMDAS is the order of operations to solve expressions involving more than one operation.
P- Parentheses.
E- Exponents.
M- Multiplication.
D- Division.
A- Addition.
S- Subtraction.
We have,
3-3x6+2
We have,
subtraction, multiplication, and addition
Using PEMDAS.
Multiplication
3 - 18 + 2
Addition
3 - 16
Subtraction
-13.
Thus the value of the expression 3 - 3x6 + 2 is -13.
Learn more about finding the value in an expression here:
#SPJ6
Answer:
1) 170,000
2) 446,220
3) 50,000
4) 7,800
Step-by-step explanation:
When we round a number to the nearest hundred then we check the digit at tens place,
If the digit is less than 5 then the number is rounded to previous thousand and if it is 5 more than 5 it is rounded to the next thousand,
While, in the case of rounding nearest ten and ten thousand we check the digit at ones place and thousand placerespectively.
1)168,356 to the nearest ten thousand is 170,000 ( ∵ thousand place digit = 8 > 5 )
2) 446,221 to the nearest ten is 446,220 ( ∵ ones place digit = 1 < 5 )
3) 45,122 to the nearest ten thousand is 50,000 ( ∵ thousand place digit = 5 ≥ 5 )
4) 7,782 to the nearest hundred is 7,800 ( ∵ tens place digit = 8 > 5 )
Answer:
altitude
Step-by-step explanation:
Answer:
(-2,8)
Step-by-step explanation:
3x+3y = 18
2x+y = 4
Multiply the second equation by -3
-3(2x+y) = -3*4
-6x-3y = -12
Add this to the first equation
3x+3y = 18
-6x-3y = -12
-------------------------
-3x = 6
Divide each side by -3
-3x/-3 = 6/-3
x = -2
Now solve for y
2x+y = 4
2(-2) +y = 4
-4+y =4
Add 4 to each side
-4+4+y = 4+4
y =8
Answer:
(-2,8)
Step-by-step explanation:
3x + 3y = 18 (1)
2x + y = 4 (2)
(1) - 3(2)
3x + 3y = 18
-(6x + 3y = 12)
-3x = 6
x = -2
Using (2)
2(-2) + y = 4
-4 + y = 4
y = 8